2012
DOI: 10.2106/jbjs.k.00006
|View full text |Cite
|
Sign up to set email alerts
|

Hemiarthroplasty of the Hip with and without Cement: A Randomized Clinical Trial

Abstract: Therapeutic Level II. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
174
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(190 citation statements)
references
References 18 publications
8
174
5
Order By: Relevance
“…The same study reported a higher perioperative mortality rate and perioperative complications in the cemented group, but this reversed with longer observation time [8]. A recent randomized controlled trial comparing an Exeter cemented (Stryker Orthopaedics, Mahwah, NJ, USA) and a Zweymüller uncemented (Centerpulse, Zurich, Switzerland) hemiarthroplasty showed a higher rate in the uncemented group of both intraoperative fractures (7.5% versus 0%) and postoperative fractures (15% versus 1.3%) within 2 years [24]. We found no differences in health-related quality of life (BI and EQ-5D), and there were no differences in ability to walk, use of analgesics, or place of living.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The same study reported a higher perioperative mortality rate and perioperative complications in the cemented group, but this reversed with longer observation time [8]. A recent randomized controlled trial comparing an Exeter cemented (Stryker Orthopaedics, Mahwah, NJ, USA) and a Zweymüller uncemented (Centerpulse, Zurich, Switzerland) hemiarthroplasty showed a higher rate in the uncemented group of both intraoperative fractures (7.5% versus 0%) and postoperative fractures (15% versus 1.3%) within 2 years [24]. We found no differences in health-related quality of life (BI and EQ-5D), and there were no differences in ability to walk, use of analgesics, or place of living.…”
Section: Discussionmentioning
confidence: 92%
“…Although the number of randomized trials is increasing, there are still problems with diversity of implants that are studied, short followup time, and interpretation of functional results versus reoperation and, maybe most important, rates of subsequent fractures [18,19,24]. The aim of this study was to examine whether the uncemented femoral stem used in this trial would perform similarly to the cemented hemiarthroplasty after 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment options include THA and bipolar hemiarthroplasty [2,12,18,26]. The optimal surgical treatment of displaced femoral neck fractures is still debated.…”
Section: Discussionmentioning
confidence: 99%
“…Controversy exists regarding the relative merits of hemiarthroplasty versus THA for patients with displaced femoral neck fractures, with some data supporting improved function in selected patients treated with THA [1,3,4,6,8,10,13,17,18,26]. It is important to understand short-and mid-term clinical results and the long-term likelihood of reoperation or revision of two commonly used treatment options, THA and bipolar hemiarthroplasty [12,18,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation